WANITA DAN KRIMINALITAS (Studi Tentang Wanita Peyalahguna Narkoba Di Lembaga Pemasyarakatan Perempuan Kelas IIA Pekanbaru) - Windy Pradini; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The background of this research comes from the author's observation of the rampant drug abuse among women, the author looks at women who are serving a sentence in the Class IIA Women’s Penitentiary.  The formulation of the problem in this study is the factor that causes women to take drugs and awareness of drug-abusing women after being detained in Pekanbaru Class IIA Women's Penitentiary. The purpose of this study was to determine the factors that cause women to take drugs and to find out the awareness of women who use drugs after being detained. This study uses descriptive quantitative research methods, the population in this study were all women who were inmates aged 18-60 years with cases of drug abusers in Pekanbaru Class IIA Women's Penitentiary. The sample in this study amounted to 67 determinants of the sample obtained from using Slovin formula. The results showed that the factors that caused women to take drugs were the biggest factor causing women to take drugs were family environmental factors or by 76.1%, awareness of drug abusers women was quite large, as evidenced by the desire to stop taking drugs at 97.0% the awareness and deterrence of drug abusers after being detained at Pekanbaru Class IIA Women's Penitentiary. Keywords: women, drugs, women’s penitentiary